Concomitant endogenous and exogenous etiology for gingival pigmentation - Panucci, Beatriz Zamboni Martins; Ferrisse, Tulio Morandin [UNESP]; Bufalino, Andreia [UNESP]; León, Jorge Esquiche (California Digital Library (CDL), 2021)
Oral pigmented lesions can be physiological or pathological, exogenous or endogenous, as well as focal, multifocal, or diffuse. Among them, the oral melanotic macule (OMM) is a small, well-delimited brown-to-black macule, often affecting the lip and gingiva. Amalgam tattoo (AT) is a grey or black area of discoloration on the oral mucosa as a result of entry of dental amalgam into the soft tissues, commonly gingiva and alveolar ridge. Herein, we present a patient with gingival pigmentation with features of both OMM and AT in the same location.
Keywords: Amalgam tattoo; Histopathology; Melanotic macule; Oral mucosa; Pigmentation disorders